Keanekaragaman Jamur Makroskopis Di Kecamatan Amahai Kabupaten Maluku Tengah - Uspitany, Lucas; Patty, Jogeneis; Uruilal, Costanza (Pattimura University Ambon Maluku Indonesia, 2024)
The research objectives are: 1) Identifying the types of macroscopic fungi found in Amahai District; 2) Calculate the frequency of presence and population of macroscopic fungi found in Amahai District, and 3) Describe the morphological characteristics of macroscopic fungi found in the Amahai sub-district. This research was carried out in Amahai District in the villages of Yafila and Nuweletetu. This research was also carried out at the Plant Disease Laboratory, Faculty of Agriculture, Pattimura University, from March to May 2024. The survey was carried out using the roaming method to obtain macroscopic fungi in Amahai District. The transect line created as a sampling location measures 100 ´ 20 m. Laboratory identification is carried out to determine the morphological characteristics of the fungus. Mushroom characteristics include fruit body shape, color, size, and habitat. The results (PCA) of 13 morphological characters from 38 fungi samples showed that between the two groups of macroscopic fungi, there was a similarity in morphological characters of 62%. Principle component analysis (PCA-Biplot) was performed on nine morphological characters on 38 macroscopic fungi samples. PCA was carried out to obtain characteristic characters in the fungi groups found. Based on the results of the analysis (PCA), the fruit's body shape and pores can be recommended as characterizing characteristics.